Intrafamillial Clustering of Helicobacter pylori Infection in Saubi Arabia - BA Al-Knawy; M-Elbagir K Ahmed; S Mirdad; A ElMekki; O Al-Ammari (Canadian Journal of Gastroenterology)
AIM: To study the pattern of Helicobacter pylori infection among family members in the Saudi population.